Prevalence of disordered eating and pathogenic weight control behaviors among NCAA Division I female collegiate gymnasts and swimmers - Anderson, C.; Petrie, T. A. (Research Quarterly for Exercise and Sport, 2012)
The purpose of this study was to survey a geographically diverse group of female collegiate athletes from two at-risk sports—swimming/diving and gymnastics. In doing so, we first wanted to examine the prevalence of clinical and subclinical disorders. Second, because relatively few athletes exhibit sufficient number and severity of symptoms to be classified as subclinical or clinical in their eating behaviors, we also wanted to determine the extent to which they engaged in pathogenic eating (e.g., bingeing) and weight control (e.g., excessive exercising, vomiting, dieting) behaviors. We selected these behaviors because they are individual symptoms of disordered eating and may be precursors to the development of subclinical or clinical disorders.